Angiotensin AT1 – α2C-Adrenoceptor Interaction Disturbs α2A-auto-Inhibition of Catecholamine Release in Hypertensive Rats - Berg, Torill (Frontiers in Neurology, 2013)
α2-adrenoceptors (AR) lower central sympathetic output and peripheral catecholamine release, and thus may prevent sympathetic hyperactivity and hypertension. α2AR also influence vascular tension. These α2AR are malfunctioning in spontaneously hypertensive rats (SHR). Here I tested if an interaction between α2AR subtypes and the angiotensin AT1 receptor (AT1R) precipitated these disorders. Blood pressure was monitored through a femoral artery catheter and cardiac output by ascending aorta flow in anaesthetized rats. Catecholamine concentrations were determined in plasma collected at the end of a 15-min tyramine-infusion. Tyramine stimulates norepinephrine release through the re-uptake transporter, thus preventing re-uptake, and presynaptic control of vesicular release is reflected as differences in overflow to plasma. Previous experiments showed surgical stress to activate some secretion of epinephrine, also subjected to α2AR-auto-inhibition. Normotensive rats (WKY) and SHR were pre-treated with 1) vehicle or α2AR antagonist (L-659,066), followed by fadolmidine (α2C>B>A+α1AR agonist), ST-91 (α2non-A-selective agonist) or m-nitrobiphenyline (α2CAR-agonist+α2A+B-antagonist), or 2) AT1R antagonist losartan, losartan+L-659,066 or losartan+clonidine. In WKY, L-659,066 alone, L-659,066+agonist or losartan+L-659,066 increased catecholamine overflow to plasma after tyramine and eliminated the norepinephrine-induced rise in total peripheral vascular resistance (TPR). In SHR, L-659,066+fadolmidine/ST-91/m-nitrobiphenyline and losartan+L-659,066 greatly increased, and losartan+clonidine reduced, catecholamine concentrations, and L-659,066+ST-91, losartan+L-659,066 and losartan+clonidine eliminated the tyramine-induced rise in TPR. Separately, these drugs had no effect in SHR. In conclusion, peripheral α2CAR-stimulation or AT1R-inhibition restored failing α2AAR-mediated auto-inhibition of norepinephrine and epinephrine release and control of TPR in SHR.